Relations between China and Latin America: From Market Opportunities to International Political Economy - Alcalde Cardoza, Javier (2016)
We perceive that a period of instability, structural change, and superpower competition is developing in the world economy and particularly in the Asia-Pacific region, following the end of the boom of Chinese growth, investment and trade (2003-2012). This boom significantly benefitted China and a number of emerging economies which sold commodities to, and hosted investment from, the PRC. The comparative stability of the former period produced in Latin America the image of economic relations with China as a relatively uncontentious issue area characterized by clear market opportunities that could be tapped largely by means of conventional diplomacy and trade expertise. There were, of course, some concerns that a new center-periphery subsystem was being established and that a small number of small or middle-size countries of the region were becoming too close to China, but these issues seldom transformed into international or domestic tensions or crises.